Spain : Selected Issues. (IMF Staff Country Reports; Country Report, 2000)
The general government in Spain is composed of the State (central) government, the social security system, 17 regional governments, and a very large number of municipalities. Over the last several years, motivated in part by a desire to qualify for participation in Stage 3 of monetary union, the Spanish authorities have achieved impressive fiscal consolidation. Between 1995 and 1999, for example, the deficit of the general government has fallen by 5.5 percent of GDP, from about 6.5 percent to about 1 percent, and the authorities aim at achieving overall fiscal balance next year.